2022
DOI: 10.3390/molecules27051498
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid–Zein Core-Shell Nanoparticles Improve the Anticancer Effect of Curcumin Alone or in Combination with Oxaliplatin against Colorectal Cancer via CD44-Mediated Cellular Uptake

Abstract: Curcumin (CUR) has been reported to enhance the chemotherapeutic efficacy of oxaliplatin (OXA) in colorectal cancer (CRC) and inhibit OXA-induced side effects. However, shortcomings, including poor solubility and sensitivity to metabolic transformation, have greatly undermined its value in clinical applications. In this study, the potential of CUR-encapsulated hyaluronic acid (HA)–zein composite nanoparticles (HZ-CUR) as an oral adjuvant for OXA-based chemotherapy was assessed in representative CRC models in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…This mechanism was verified through the assay of the curcumin intracellular content after the inhibition of the expression of CD44, where the results showed significant reduction in the curcumin intracellular content in the HCT116 and HT29 cells. This showed that the endocytosis mechanism is important for the HZ-CUR nanoparticles uptake [66].…”
Section: Examples For the Effect Of Zein Nanoparticles On Different T...mentioning
confidence: 89%
“…This mechanism was verified through the assay of the curcumin intracellular content after the inhibition of the expression of CD44, where the results showed significant reduction in the curcumin intracellular content in the HCT116 and HT29 cells. This showed that the endocytosis mechanism is important for the HZ-CUR nanoparticles uptake [66].…”
Section: Examples For the Effect Of Zein Nanoparticles On Different T...mentioning
confidence: 89%
“…The oHA can compete for the binding of endogenous HA to CD44 by inhibiting the MDR and other ABC transporter protein expression, breaking the "HA-CD44" barrier in vivo, reversing the chemotherapy resistance of tumors, and penetrating the colonic mucosa more potently to play a role. Liu et al [85] assessed the potential of CUR-encapsulated HA-zein composite nanoparticles (HZ-CUR) as an oral adjuvant for OXA-based chemotherapy in representative CRC models in mice. The specific recognition/interaction between HA and CD44 contributes to the tumor-targeting property of HA-coated nanocarriers.…”
Section: Oral Nano-formulations For Overcoming Intestinal Barriersmentioning
confidence: 99%
“…This nding veri ed active targeting of CD44 receptor in C26 cells via HA as a ligand. Other studies have also reported the uptake of HA-decorated NPs by CD44-mediated endocytosis [24,37,38]. For instance, Shahriari et al indicated that the HA-coated platform is able to enhance the cellular internalization and cytotoxicity against CD44 overexpressing 4T1 cells [26].…”
Section: Flow Cytometry Studymentioning
confidence: 99%